Dealing with Functional Diversity in EFL Classrooms: English Teachers’ Positioning - Villarreal Buitrago, Laura Camila; Méndez Rivera, Pilar Esther (Colombian Applied Linguistics Journal, 2021)
Functional Diversity (FD) and inclusion are nowadays widely explored subjects, specifically in the field of English language teaching. This article examines the ways in which EFL teachers problematize their role in functionally diverse scenarios while exposing their efforts to improve the exercise of their profession in FD classrooms. By applying positioning theory (Harré, 2001), we analyzed the narratives of four English language teachers at a high school in Bogotá, Colombia. Data obtained from autobiographical narrative essays revealed three main findings: first, English language teachers positioned themselves as novice or apprentice in FD contexts; second, they struggled with their unpreparedness as they learned to work with FD students; and finally, they positioned themselves as agents of change to overcome difficulties and embrace an inclusive pedagogy. This study contributes to the field by raising awareness of real teaching problems and school situations that EFL teachers face, specifically those related to the struggles of the self (Méndez, 2017).